Protective effects of caffeic acid phenethyl ester on the dose‐dependent acute nephrotoxicity with paraquat in a rat model. Issue 3 (21st November 2013) - Rifaioglu, Murat Mehmet; Sefil, Fatih; Gokce, Hasan; Nacar, Ahmet; Dorum, Bayram Ali; Davarci, Mursel
ABSTRACT Paraquat (PQ), which is used extensively as a potent herbicide throughout the world, is highly toxic in humans. We aimed to determine PQ‐induced biochemical and histologic changes in the kidneys, and to evaluate the ability of the protective effects of caffeic acid phenethyl ester (CAPE) against PQ‐induced injury in rats. Forty‐eight rats were divided into eight groups of six: Group 1: Control; Group 2: 10 μmol/kg CAPE; Group 3: 15 mg/kg PQ; Group 4: 30 mg/kg PQ; Group 5: 45 mg/kg PQ; Group 6: 15 mg/kg PQ+CAPE; Group 7: 30 mg/kg PQ+CAPE; Group 8: 45 mg/kg PQ+CAPE. PQ and CAPE were injected intraperitoneally. The levels of the total oxidant status (TOS) and total antioxidant status (TAS) were determined in the supernatants of the excised left kidney. Right kidney tissue of each rat was removed to obtain a histologic score. When PQ‐administrated (15, 30, 45) groups compared with other groups, TOS values were found to be significantly higher (p < 0.01). PQ (15, 30, 45) groups had significantly diminished values of TAS than the other groups (p < 0.001). Of histologic score evaluation, only the PQ45 group had a significantly higher value than the sham, and CAPE groups (p < 0.05). Moreover, in CAPE+PQ45 group, the level of histologic score was decreased compared to PQ45 group (p < 0.001). In conclusion, the evaluation of the data suggests that CAPE can be used to prevent the acute effects of PQ nephrotoxicity. © 2013 Wiley Periodicals, Inc. Environ Toxicol 30: 375–381, 2015.